Importance of ecosystem services and ecological security patterns on Hainan Island, China - Liu, Haodong; Zhang, Gaoqiang; Li, Tianqi; Ren, Siyuan; Chen, Baihua; Feng, Kaibin; Li, Wei; Zhao, Xiaoqing; Qin, Pengyao; Zhao, Junpeng (Frontiers in Environmental Science, 2024)
The identification and restoration of damaged ecosystems are key to achieving ecological conservation and sustainable. Hainan Island is experiencing a serious crisis of biodiversity and habitat degradation. Therefore, its ecological conservation has become a priority and challenge for China. This study aimed to construct a multi-level ecological security pattern (ESP) based on the synergy of multiple ecosystem service functions and identify important ecological elements and ecological restoration areas. Based on the InVEST model, the circuit theory model, and a series of GIS spatial analysis methods, the importance of ecosystem functions (biodiversity maintenance, water conservation, carbon sequestration, and soil conservation) was evaluated, and ecological sources, ecological corridors, ecological pinch points, and ecological barrier points were identified. The results are as follows: 1) The best habitats in Hainan Island were distributed in the central mountainous area with diverse ecosystems, with an area of 10982.5 km2, accounting for 34.25% of the total suitable habitats. Low-level habitats are mainly distributed on tableland and coastal zones. Human disturbance is the direct cause of landscape patch fragmentation in low-level habitat areas. 2) A total of 65 large ecological sources with a total area of 8238.23 km2 were identified, which were concentrated in the biodiversity and water conservation areas in the central part of the island. 3) Crucial areas in Hainan Island mainly comprised forests and water bodies. Ecological corridors radiated across the entire area in the form of a spider web and connected all important ecological patches, including 138 ecological corridors (73 primary ecological corridors and 65 secondary ecological corridors), 222 ecological pinch points, and 198 ecological barrier points. In addition, the identified areas for restoration are primary areas in urgent need of protection and restoration. In general, the ecological pinch points are natural conservation areas supplemented by anthropogenic restoration, and the ecological barrier points demand equal attention for anthropogenic restoration and nature conservation. The ecosystem protection plan developed in this study will enrich the theoretical achievements of territorial spatial ecological planning in Hainan Island, and provides clear guidance for alleviating the contradiction between land use and economic development in Hainan Island.